Meningkatkan Pengetahuan Dan Motivasi Masyarakat Pesisir Dalam Memanfaatkan Pelayanan Kesehatan - Nopia Wati; Henni Febriawati; Riska Yanuarti; Oktavia, Desi; Mira Pitaloka; Tiwi Agustin; Chandra Widiatni Pramita; Nurul Izzah; Mirando Juney Prayogo (Gayaku Publisher, 2024)
The community typically visits health services only when they are sick, yet they rarely undergo routine health check-ups, and they do not seek medical attention even when they show early symptoms of illness. The method used in this activity is health counseling to increase the coastal community's knowledge about health services. The participants showed great enthusiasm during the activity. Based on the questions asked, the community gained a better understanding of the importance of utilizing health services. Previously, they only used health services when ill, but now they are more motivated to take advantage of health services for prevention. From the questions raised, the participants were able to provide correct answers. According to the results of the questionnaires distributed, the participants were able to demonstrate increased awareness. A major health issue in coastal communities is their lack of awareness about the importance of monitoring their health. The community tends to visit health services only when they feel sick, and many do not seek medical attention even after experiencing symptoms of illness.